2007
DOI: 10.1152/ajpregu.00517.2006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholecystokinin-8s in the nucleus tractus solitarius of vagally deafferented rats

Abstract: Baptista V, Browning KN, Travagli RA. Effects of cholecystokinin-8s in the nucleus tractus solitarius of vagally deafferented rats. Am J Physiol Regul Integr Comp Physiol 292: R1092-R1100, 2007. First published November 22, 2006; doi:10.1152/ajpregu.00517.2006.-We have shown recently that cholecystokinin octapeptide (CCK-8s) increases glutamate release from nerve terminals onto neurons of the nucleus tractus solitarius pars centralis (cNTS). The effects of CCK on gastrointestinal-related functions have, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 65 publications
6
76
0
Order By: Relevance
“…The well-accepted mechanism of CCK-induced gastroinhibition suggests that CCK-8s activates C-type vagal afferent fibers via a paracrine mechanism, since capsaicin attenuates, or even abolishes, the effects of systemic CCK-8s (34,50,61). Several studies, however, have reported direct effects of CCK-8s on brain stem circuits (4,6,7,13,48,79). Our data imply that at least some of the effects of CCK-8s on gastric tone and the modulation of the esophageal-gastric reflex may be due to a direct effect of CCK-8s on brain stem neurocircuitry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-accepted mechanism of CCK-induced gastroinhibition suggests that CCK-8s activates C-type vagal afferent fibers via a paracrine mechanism, since capsaicin attenuates, or even abolishes, the effects of systemic CCK-8s (34,50,61). Several studies, however, have reported direct effects of CCK-8s on brain stem circuits (4,6,7,13,48,79). Our data imply that at least some of the effects of CCK-8s on gastric tone and the modulation of the esophageal-gastric reflex may be due to a direct effect of CCK-8s on brain stem neurocircuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral, biochemical, and electrophysiological studies have shown that a relevant portion of the gastrointestinal effects of sulfated CCK (CCK-8s) are due to direct actions at the level of brain stem vagal circuits. In fact, CCK-8s acts on vagal afferent fibers that synapse on NTS neurons as well as at the level of subpopulations of NTS and DMV neurons (4,6,7,9,12,13,48,51,71,74,75,79). These studies suggest that functional CCK-A receptors are present on the membrane of subgroups of NTS and gastric-projecting DMV neurons.…”
mentioning
confidence: 81%
“…Interestingly, however, as mentioned previously, application of DB to GI cells stimulates the release of CCK (8,18). While CCK is generally considered a satiety hormone that exerts its effects through both vagal and nonvagal (humoral) routes at various peripheral and central targets (3,27,34), it is also believed to convey stimulusspecific information in a paracrine fashion at local sensory afferent terminals (15,36). If CCK is involved as a critical chemosensory signaling component, then pretreatment with devazepide, a CCK-1R antagonist, should abolish the early response to intraduodenal DB, compared with pretreatment with its vehicle.…”
Section: Experiments 1: Rats Rapidly Suppress Ongoing Intake In Re-mentioning
confidence: 92%
“…Surgical vagal deafferentation was achieved by sectioning the vagal afferent nerve rootlets (supranodose afferent rhizotomy) in six rats using a technique described previously Baptista et al, 2007). Rats were anesthetized with an intramuscular injection of a mixture of ketamine/xylazine/acepromazine (80, 1.6, 5 mg/ml/kg Ϫ1 , respectively) and placed in a stereotaxic frame.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the classical satiety hormone cholecystokinin (CCK) and the longer-lasting ␣MSH synthetic analog melanotan II (MTII) use the cAMP-ERK (extracellular signal-regulated kinase)-cAMP response elementbinding protein cascade in NTS circuits as a common pathway to integrate satiety signals from the gut and adiposity signals from the hypothalamus in the control of meal size and food intake (Sutton et al, 2005). We have also shown that CCK modulates NTScentralis neurons via an increase of glutamatergic synaptic inputs (Baptista et al, 2005a(Baptista et al, , 2007, an effect that occurs also in POMC neurons of the caudal NTS (Appleyard et al, 2005).…”
Section: Introductionmentioning
confidence: 99%